Coping with Shocks and Shifts: The Multilateral Trading System in Historical Perspective. - Irwin, D; O'Rourke, K (Nuffield College (University of Oxford), 2011)
This paper provides a historical look at how the multilateral trading system has coped with the challenge of shocks and shifts. By shocks we mean sudden jolts to the world economy in the form of financial crises and deep recessions, or wars and political conflicts. By shifts we mean slow-moving, long-term changes in comparative advantage or shifts in the geopolitical equilibrium that force economies to undergo disruptive and potentially painful adjustments. We conclude that most shocks (financial crises and regional wars) have had relatively little effect on the trade policy, but that shifts pose a greater challenge to the system of open, ultilateral trade.